Differences in physiological integration between invasive and noninvasive introduced clonal species of Carpobrotus. (17th June 2019) - Roiloa, Sergio R; Alpert, Peter; Barreiro, Rodolfo
Abstract: Aims: Clonal growth is associated with invasiveness in introduced plant species, but few studies have compared invasive and noninvasive introduced clonal species to investigate which clonal traits may underlie invasiveness. To test the hypothesis that greater capacity to increase clonal growth via physiological integration of connected ramets increases invasiveness in clonal plants, we compared the effects of severing connections on accumulation of mass in the two species of the creeping, succulent, perennial, herbaceous genus Carpobrotus that have been introduced on sand dunes along the Pacific Coast of northern California, the highly invasive species Carpobrotus edulis and the co-occurring, noninvasive species Carpobrotus chilensis . Methods: Pairs of ramets from four mixed populations of the species from California were grown in a common garden for 3 months with and without severing the stem connecting the ramets. To simulate the effect of clones on soils in natural populations, the older ramet was grown in sand amended with potting compost and the younger in sand alone. Important Findings: Severance decreased net growth in mass by 60% in C. edulis and 100% in C. chilensis, due mainly to the negative effect of severance on the shoot mass of the younger ramet within a pair. Contrary to the hypothesis, this suggests that physiological integration increases growth more in the less invasive species. However, severance also decreased allocation of mass to roots in the older ramet and increased it in the younger ramet in a pair, and the effect on the younger ramet was about twice as great in C. edulis as in C. chilensis . This indicates that the more invasive species shows greater phenotypic plasticity in response to physiological integration, in particular greater capacity for division of labor. This could contribute to greater long-term growth and suggests that the division of labor may be a trait that underlies the association between clonal growth and invasiveness in plants.